Direct power control of DFIG wind turbine systems based on an intelligent proportional-integral sliding mode control. (September 2016) - Li, Shanzhi; Wang, Haoping; Tian, Yang; Aitouch, Abdel; Klein, John
Abstract: This paper presents an intelligent proportional-integral sliding mode control (iPISMC) for direct power control of variable speed-constant frequency wind turbine system. This approach deals with optimal power production (in the maximum power point tracking sense) under several disturbance factors such as turbulent wind. This controller is made of two sub-components: (i) an intelligent proportional-integral module for online disturbance compensation and (ii) a sliding mode module for circumventing disturbance estimation errors. This iPISMC method has been tested on FAST/Simulink platform of a 5 MW wind turbine system. The obtained results demonstrate that the proposed iPISMC method outperforms the classical PI and intelligent proportional-integral control (iPI) in terms of both active power and response time. Highlights: An iPISMC strategy is proposed for power control of wind turbine systems. The relation between dynaimcal power and current is regarded as one-order and a LUD. To reduce estimation error of LUD, an extra sliding mode control is proposed. Comparing to iPI and PI, iPISMC reduces steady error and has a better performance.